Usefulness of Organic Acid Produced by Exiguobacterium sp. 12/1 on Neutralization of Alkaline Wastewater - Niha Mohan Kulshreshtha; Anil Kumar; Gopal Bisht; Santosh Pasha; Rita Kumar (The Scientific World Journal)
The aim of this study was to investigate the role of organic acids produced by Exiguobacterium sp. strain 12/1 (DSM 21148) in neutralization of alkaline wastewater emanated from beverage industry. This bacterium is known to be able to grow in medium of pH as high as pH 12.0 and to neutralize alkaline industrial wastewater from pH 12.0 to pH 7.5. The initial investigation on the type of functional groups present in medium, carried out using FT-IR spectroscopy, revealed the presence of peaks corresponding to carbonyl group and hydroxyl group, suggesting the release of carboxylic acid or related metabolic product(s). The identification of specific carboxylic group, carried out using RP-HPLC, revealed the presence of a single peak in the culture supernatant with retention time most similar to formic acid. The concentration of acid produced on different carbon sources was studied as a function of time. Although acid was present in same final concentration, the rate of acid production was highest in case of medium supplemented with sucrose followed by fructose and glucose. The knowledge of metabolic products of the bacterium can be considered as a first step towards realization of its potential for large-scale bioremediation of alkaline wastewater from beverage industry.